Remittances and income diversification in Bolivia's rural sector - Lazarte Alcala, Naneida Regina; Adkins, Lee C.; Lahiri, Bidisha; Savvides, Andreas (My University, 2014)
This article examines the role of remittances in income diversification strategies in Bolivia's rural sector. Remittances can be consumed or invested by the recipient. As an investment, funds can be used for farming or to finance other nonfarm productions. In this article, we use a large and nationally representative survey to estimate the effect that remittances have on the probability of producing income from nonfarm activities (diversification) by using a bivariate probit model. Our evidence shows that remittances increase the probability that a rural family engages in nonfarm activities, at least in some regions of Bolivia. We also find evidence that the sender's decision to remit and the recipient's decision to diversify may be jointly determined. As such, this suggests that remittances may serve as a mechanism to overcome localized failures in Bolivia's capital markets.
Keywords: Bolivia; Income diversification; Latin America; Remittances; Rural-urban migration